Ethics review of research on humans in the biomedical and non-biomedical sciences: bridging "two cultures" in Brazil? (Práxis Educativa, 2023)
The ethics regulation of human-subject research in Brazil is by the Research Ethics Committee (CEP)/National Commission of Research Ethics (CONEP) System. While primarily focusing on biomedical research, this System also oversees the ethics of non-biomedical research. However, a distinct clash between these two research cultures is evident in Brazil. Despite existing guidelines, the cultural clash between biomedical and the humanities and social sciences (HSS) research has fueled discussions that include separating HSS research from the oversight of the CEP/CONEP System. We investigated perceptions of this ethics regulatory framework, focusing on HSS. A survey was conducted among coordinators of HSS graduate programs in six Brazilian public universities. We found growing awareness of and willingness to address the ethical aspects of human-subject research. Paradoxically, the ongoing conflictual debate seems to be gradually bridging the gap between these two cultures and feeding transformative changes to ethics regulation in HSS human-subject research in Brazil.Keywords: Research ethics. Human-subject research. Graduate programs.